2009
DOI: 10.1016/s1808-8694(15)30828-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein-Barr virus in recurrent tonsillitis

Abstract: children's tonsils can be colonized by EBV and such colonies may be associated with the pathogenesis of recurrent tonsillitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 17 publications
4
24
1
2
Order By: Relevance
“…The results are not encouraging since we detect EBV in only 5 cases (11%) and in few cells within the interfollicular area. This finding is less than that reported by Dias et al [16], indicating a lesser expression of LMP-1 in EBV infected cells. In addition, it indicates that using EBER-ISH is the gold standard for detecting EBV in tissue.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The results are not encouraging since we detect EBV in only 5 cases (11%) and in few cells within the interfollicular area. This finding is less than that reported by Dias et al [16], indicating a lesser expression of LMP-1 in EBV infected cells. In addition, it indicates that using EBER-ISH is the gold standard for detecting EBV in tissue.…”
Section: Discussioncontrasting
confidence: 73%
“…Recurrent bacterial tonsillitis is considered to be the main reason for the enlargement of the tonsils; however, the bacteriological examinations of the tonsils showed that the relationship is not very clear [15]. Misuse of antibiotic therapy in acute tonsillitis may lead to change in tonsillar microflora and predisposing to recurrent tonsillitis and subsequent colonization by various bacteria and viruses [16]. The role of Actinomycosis is considered in the etiology of recurrent tonsillitis, not as an active infection but as a factor in the development of lymphoid hyperplasia and hypertrophy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Tonsils are also suggested to be the onset and replication site for the infections [8]. In our study, we found out that EBV was positive most frequently in tonsillar samples of children with recurrent tonsillitis (53.8%) using real-time PCR.…”
Section: Discussionmentioning
confidence: 51%
“…In various studies, EBV has been identified as one of the most frequently met viral agents which cause recurrent tonsillitis [7][8][9][10]. Tonsils are also suggested to be the onset and replication site for the infections [8].…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic effects have been documented in some of human viruses. In tumour cells Epstein-Barr virus (EBV) has been indetified that causes nasopharynx cancer and Burkitt lymphoma, while the most recent research indicate that EBV participates in etiopathogenesis of stomach cancer, Hodgkin's lymphoma, as well as palatine tonsil cancer and tongue cancer [17,28,32]. Moreover, it has been proved that human Herpesvirus type 8 (HHV8) is etiopathogenetically related to Kaposi's sarcoma that develops in Acquired Immune Deficiency Syndrome (AIDS) [5,28,30].…”
Section: Discussionmentioning
confidence: 99%